Hole Geometrical at Glass Fiber Reinforced Polymer Laminate Affected by Parameter of Drill Process - Astika, I Made; Sukadana, I Gusti Ketut (Jurnal Energi Dan Manufaktur, 2012)
Fiber Reinforced Composite (FRC) is mostly applied such as the low density and high elastic strain of glass fiber reinforcedcomposite (GFRC) or glass fiber reinforced polymer (GFRP). Although GFRP can be made as initial design, the finalmachining processes is still needed such as hole drilling component. The hole drilling machining process consisted of manyparameters such as cutting speed (v) and feed rate (fz). These parameters can influence the geometrical characteristics ofproduct such as the accurate dimension of hole or even the geometrical defect.In this case it is necessary to investigate theeffect of feed rate (fz) to the geometrical of hole on GFRP laminate. The feed rate was varied as 0.1, 0.18 and 0.24 mm/rwith diameter of drilling tool is 5 mm. The material composite was glass fiber with woven roving and it was lied into 10 layerwith a thickness of 4 mm. Yukalac 157BQTN-EX with Mekpox hardener was use for matrix. The mold process was a handlay-up.The result showed that the maximum damage of product was found when the maximum feed rate of 0.24 mm/r wasoperated. The damage found was inaccurate size/dimension on hole and geometrical defect of hole (elliptical shape).
Keywords: GFRP laminate, Drilling, Feed rate, Geometrical of hole